(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Many questions might confront any researcher, who is interested to have his results presented in front of his eyes in an appealing way. Questions such as: How far can he exploit the visualization software to show, experts and non-expert people, his findings or results in a convincing way? Is this visualization software is the proper one for his tasks? Can this visualization process play an important and active role in the interpretation process OR is it only a final stage for showing others some pretty colored figures, pictures and animations. Furthermore, it is known that visualization can be considered as one of the final stages in the process of handling any kind of geophysical and remote sensing data. However, many researchers in this field consider that visualization is a luxury phase during the major data handling. Many of them deny that it is part of the interpretation process. We try here to prove the opposite. To do so, five projects were discussed in this work are: Creation of DTM for whole Iraq and surrounding, Uplifting deformation due to hydraulic head difference in a faulted area. Monitoring of deformations in a water barrier dike in the Netherlands, Evaluation of Two Laser Altimetry surveys (AHN1 and AHN2) in the Netherlands. Presentation of atmospheric water vapor of Mexico City for InSAR signal corrections, It is concluded in this work that visualization process, using Fledermaus software, proved to be quite impressive and important stage especially when there is a huge amount of data to handle. Its ability to - calculate the statistical parameters to describe the surface, creating profiles, draping different layers or surfaces on each other, gridding non gridded data, the ability to make comparison and/or correlation between the different obtained surfaces/layers, handling 2D/3D polygon lines, differentiating and handling many data formats, converting / editing geo-references and many other features. All of these features with addition to the direct interactive display of the data add an extra momentum which leads to the conclusion that the visualization stage should be considered as part of the interpretation process.